Using Patient-Reported Outcome Measures (PROMs) to promote quality of care and safety in the management of patients with Advanced Chronic Kidney disease (PRO-trACK project): a mixed-methods project protocol. Issue 6 (30th June 2017) - Aiyegbusi, Olalekan Lee; Kyte, Derek; Cockwell, Paul; Marshall, Tom; Dutton, Mary; Slade, Anita; Marklew, Neil; Price, Gary; Verdi, Rav; Waters, Judi; Sharpe, Keeley; Calvert, Melanie
Abstract : Introduction: Advanced chronic kidney disease (CKD) has a major effect on the quality of life and health status of patients and requires accurate and responsive management. The use of electronic patient-reported outcome measures (ePROMs) could assist patients with advanced pre-dialysis CKD, and the clinicians responsible for their care, by identifying important changes in symptom burden in real time. We report the protocol for 'Using Patient-Reported Outcome measures (PROMs) to promote quality of care and safety in the management of patients with Advanced Chronic Kidney Disease' (PRO-trACK) project, which will explore the feasibility and validity of an ePROM system for use in patients with advanced CKD. Methods and analysis: The project will use a mixed-methods approach in three studies: (1) usability testing of the ePROM system involving up to 30 patients and focusing on acceptability and technical performance/stability; (2) ascertaining the views of patient and clinician stakeholders on the optimal use and administration of the CKD ePROM system—this will involve qualitative face-to-face/telephone interviewing with up to 30 patients or until saturation is achieved, focus groups with up to 15 clinical staff, management and IT team members; (3) psychometric assessment of the system, within a cohort of at least 180 patients with advanced CKD, to establish the measurement properties of the ePROM. Ethics and dissemination: This project was approved by the West Midlands Edgbaston Research Ethics Committee (Reference 17/WM/0010) and received Health Research Authority (HRA) approval on 24 February 2017. The findings from this project will be provided to clinicians at the Department of Renal Medicine, Queen Elizabeth Hospitals, Birmingham (QEHB), NHS England, presented at conferences and to the Kidney Patients' Association, British Kidney Patient Association and the British Renal Society. Articles based on the findings will be written and submitted for publication in peer-reviewed journals.